DESIGN OF WASTEWATER COLLECTION SYSTEM FOR DURA TOWN - SULTAN, BAHER; GHIATH, SAFA'A; Al-Hammouri, Mohanad (جامعة بوليتكنك فلسطين - كلية الهندسة - مساحة, 2006)
There is no wastewater collection system at present in Dura town. The sewage from residential and public buildings in the area is drained to cesspits. These have become clogged with time and require frequent emptying. The continued use of cesspits with the icrease in population will cause environmental and health problem, and may create contamination of the underground water aquifer. Furthermore, emptying csspools constitutes an offensive odor nuisance to the population. On the other hand, emptying the vacuum trunks in the nearly wadi causes negative impacts on the visual landscape. In reference to above description of the existing situation, there is a clear need of project in order to improve the sanitary level in Dura town. The first step is serving the city with wastewater collection system. So, the main objective of this project is to design wastewater collection network for Dura town of the Hebron district. The present study considered the annual population growth and their water consumption for the coming 25 years that will be the design period, along with the commercial and industrial development in the area. The necessary hydraulic calculation needed for the design of the main trunks was carried out by simple calculation. The results of the study show that wastewater disposal in Dura area causes problems to the peoples; subsequently there is a big need for immediate steps for construction of the proposed wastewater collection system. Gravity flow sanitary sewer was proposed for most of Dura areas to minimize the cost of construction and excavations with two pumping stations.
no of pages 62 , مساحة 4/2006
Keywords: WASTEWATER COLLECTION SYSTEM